2019
DOI: 10.1021/acs.macromol.8b01874
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Short-Chain Branched Bimodal Polyethylene: Topological Characteristics and Mechanical Behavior

Abstract: It has previously been shown that polyethylene (PE) with a bimodal molar mass distribution has a high fracture toughness. Our approach has been to use coarse-grained (CG) molecular dynamics (MD) simulations to investigate the effects of including short-chain branches in the high molar mass fraction of bimodal PE on topological features and mechanical behavior of the material. The CG potentials were derived, validated, and utilized to simulate melt equilibration, cooling, crystallization, and mechanical deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 77 publications
4
47
0
Order By: Relevance
“…For reference, the simulation-based literature on polymer crystallization (e.g., [16,[18][19][20]24,25,28,30,34,38,41,42,48]) does not provide a clear precedent as to whether or not such short stems should be included when analyzing polymer crystallization simulations. In particular, some studies include such short stems [18,24,25,28,38,41,42,48], other studies exclude them by invoking a minimum length criterion [16,21,22,34], and still other studies allow for stems of variable length and use a length criterion to assign some stems as crystalline [19,20,30]. Therefore, we assessed the role of single-bead stems in the formation of large, post-critical crystal clusters.…”
Section: Pressure 1 Atmmentioning
confidence: 99%
See 1 more Smart Citation
“…For reference, the simulation-based literature on polymer crystallization (e.g., [16,[18][19][20]24,25,28,30,34,38,41,42,48]) does not provide a clear precedent as to whether or not such short stems should be included when analyzing polymer crystallization simulations. In particular, some studies include such short stems [18,24,25,28,38,41,42,48], other studies exclude them by invoking a minimum length criterion [16,21,22,34], and still other studies allow for stems of variable length and use a length criterion to assign some stems as crystalline [19,20,30]. Therefore, we assessed the role of single-bead stems in the formation of large, post-critical crystal clusters.…”
Section: Pressure 1 Atmmentioning
confidence: 99%
“…With molecular simulations, one can directly study the molecular-level nanoscopic details of polymer crystal nuclei and stems during polymer crystallization. Previous in silico studies have probed stem-related properties and phenomena during crystallization, including the lamellar thickness of nuclei [14,15], intra-lamellar stem reordering mechanisms [16], stem growth rates as a function of stem length [16,17], the structural details of crystal growth fronts [16,18,19], and connections between average stem lengths and crystallization conditions (e.g., temperature and system composition) [20][21][22][23]. In particular, Doye and Frenkel [24] studied the distribution of stem lengths during the formation of crystalline layers from solution on polymer crystal growth faces of varying thickness, and thereby revealed that stem lengths can vary substantially.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Therefore, it was assumed that charge transport in the LDPE occurs dominantly in amorphous regions with higher concentrations of impurities, i.e. along the crystalline lamellar layers in the spherulites, 41 and along spherulite boundaries. [42][43][44][45] In the FEM model, the conductive paths were considered to exist dominantly in the thin amorphous regions along the spherulite boundaries.…”
Section: Inuence Of Morphology and Oxidation On The DC Conductivity mentioning
confidence: 99%
“…Therefore, in this atomic study, isotactic PP model was constructed in a cube with the dimensions of 8.0 nm × 8.0 nm × 8.0 nm. It is reported that PP has a semicrystalline structure with different crystallite sizes (>10 nm) and the amorphous phase [ 20 , 21 ]. In this present work, the PP structure was simplified as amorphous phases in small calculated volumes.…”
Section: Methodsmentioning
confidence: 99%
“…It has become a promising tool for observing the atomic movements that are allowed to interact and giving a view of the dynamic evolution at atomic level. Moyassari et al [ 20 , 21 ] used coarse-grained MD simulations method for the short-chain branched bimodal polyethylene and the linear polyethylene blend systems to investigate the topological features and mechanical behaviors of the semi-crystalline polymer. By using the fully atomistic MD simulations with the reactive force field (ReaxFF), Rout et al [ 22 ] studied the interface joining of metal and polymer during the mechanical friction process in order to check whether chemical bond between polymer and metal is formed.…”
Section: Introductionmentioning
confidence: 99%